2014
DOI: 10.1583/13-4420r.1
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel-Eluting Balloon vs. Standard Angioplasty to Reduce Recurrent Restenosis in Diabetic Patients With In-Stent Restenosis of the Superficial Femoral and Proximal Popliteal Arteries: The DEBATE-ISR Study

Abstract: Using DEB for treating femoropopliteal ISR led to a significant reduction in recurrent restenosis and repeat angioplasty at 1-year follow-up as compared to historical controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
89
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(90 citation statements)
references
References 22 publications
1
89
0
Order By: Relevance
“…The majority of previously assessed data on SFA ISR treatment have not been convincing. Results have been derived from single-arm observations (DCBA 12,13 ), historical comparisons (DCBA versus POBA 14 ), subgroup analyses (drug-eluting stent 18 ), studies on specific lesions (chronic total occluded ISR 19 ), and initial experiments (cutting balloon versus POBA 17 ). In some cases, high rates of bailout stenting (10% 13 and 15.9% 14 ) or additional laser mediated debulking (10% 13 ) weaken the significance of the findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of previously assessed data on SFA ISR treatment have not been convincing. Results have been derived from single-arm observations (DCBA 12,13 ), historical comparisons (DCBA versus POBA 14 ), subgroup analyses (drug-eluting stent 18 ), studies on specific lesions (chronic total occluded ISR 19 ), and initial experiments (cutting balloon versus POBA 17 ). In some cases, high rates of bailout stenting (10% 13 and 15.9% 14 ) or additional laser mediated debulking (10% 13 ) weaken the significance of the findings.…”
Section: Discussionmentioning
confidence: 99%
“…In a small, prospective registry of DCBA for SFA ISR, 12,13 recurrent restenosis rates were 7.9% (4 of 39) and 29.7% (11 of 37) at 12 and 24 months, respectively. For diabetic patients, Liistro et al 14 reported significantly lower recurrent ISR rates at 12 months after DCBA compared with a historical POBA group (19.5% [8 of 41] …”
Section: Editorial See P 2198 Clinical Perspective On P 2236mentioning
confidence: 99%
“…94 Long-term stent implantation triggers smooth muscle cell migration and 95 Hence, there is still an unmet demand for development of novel materials to antagonize in-stent restenosis and thrombosis. [95][96][97][98] Thus, the nanocomposites which hold a great potential to improve stent hemocompatibility can be considered as a putative candidate for developing cardiovascular stents.…”
Section: Nanocomposites To Improve Hemocompatibility Of Stentmentioning
confidence: 99%
“…The DEBATE-ISR (Drug Eluting Balloon in Peripheral Intervention for In-Stent Restenosis) RCT utilized DCB in 44 and PTA in 42 patients, with similar lesion lengths (175±90 mm vs. 160±82 mm; p= 0.4), percentage of CLI patients (75 % vs. 67 %; p=0.8), and provisional stent use (16 % vs. 26 %; p=0.2), respectively [30]. Of note, the disease severity was markedly higher in this study compared with aforementioned de novo RCT examining DCB.…”
Section: Drug-coated Balloonsmentioning
confidence: 99%